Graft Modification Strategies to Improve Patency of Prosthetic Arteriovenous Grafts for Hemodialysis. Issue 1 (March 2016) - Moufarrej, Andrew; Tordoir, Jan; Mees, Barend
Prosthetic arteriovenous grafts (AVGs) are indicated for vascular access for long-term hemodialysis in patients in whom creation or maintenance of an arteriovenous fistula (AVF) has failed or is contraindicated. AVGs have an inferior long-term patency as compared to AVFs. To ameliorate patency rates of prosthetic AVGs, different strategies have emerged to improve graft materials. This review aims to describe current strategies and future perspectives on graft modification, by graft geometry, drug coatings and graft surface technology, to improve AVG patency.